Sri Lanka and Malaysia - Bruton, Henry J.; World Bank. (Oxford ; New York : Published for the World Bank [by] Oxford University Press, 1992)
This volume is a part of a series of country studies on poverty, equity, and growth sponsored by the World Bank. Bruton analyzes the pattern of economic growth in Sri lanka and Malaysia during the period 1950 to 1980 within the context of their initial resource endowment, economic structure, social and political institutions, and forms of economic organizations. Emphasis is placed on examining the effect of economic growth on the important aspects of equity and poverty. Although the statistical data used pertains to 1985, the conclusions reached and recommendations made for the economies still seem valid.
Includes bibliographical references (p. 405-413) and index.
oif 05/05/15
Loan
Keywords: Sri Lanka -- Economic conditions; Sri Lanka -- Economic policy; Income distribution -- Sri Lanka; Poor -- Sri Lanka; Malaysia -- Economic conditions; Malaysia -- Economic policy; Income distribution -- Malaysia; Poor -- Malaysia